1984
DOI: 10.1055/s-2008-1025888
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption and Speed of Cycling Using an Air-Resistance Simulator on a Hometrainer Roller

Abstract: Oxygen consumption was determined for subjects cycling on a hometrainer roller with a racing bicycle. In part of the experiments the bicycle was supplied with an air-resistance simulator. The relation between oxygen consumption and velocity of cycling on the roller is linear: similar to that during bicycle ergometry. The relation is almost the same as during bicycling outdoors on a touring bicycle when the simulator is used while cycling on the roller. Cycling with the simulator only on the bicycle on a suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The study populations considered in these publications totalled 670 subjects. The running test was also applied to 274 children and adolescents (5,6,7). Subjects varied widely i n athletic ability, from sedentary individuals to world-class athletes (see Table 1).…”
mentioning
confidence: 99%
“…The study populations considered in these publications totalled 670 subjects. The running test was also applied to 274 children and adolescents (5,6,7). Subjects varied widely i n athletic ability, from sedentary individuals to world-class athletes (see Table 1).…”
mentioning
confidence: 99%
“…The rotating fans created wind resistance by impelling air. The speed/power output relationship using this type of wind-load simulator has been reported to be similar to that described in track cycling (Oude Vrielink et al 1984) and has been used by several authors (Gore et al 1996;Hue et al 2001). The saddle was individually adjusted to optimize rider comfort and performance, and the chainrings were equipped with standard pedals.…”
Section: One-km All-out Testmentioning
confidence: 79%
“…This was reinforced by the relatively high mechanical values recorded at the end of the test (i.e., after 1 min of supramaximal effort). However, the Cycletrack has been validated by Oude Vrielink et al (1984) for ergometry and training. These authors reported similar VO 2 and cycling velocity on a roller system with air-resistance simulation as during cycling outdoors on a touring bicycle.…”
Section: Discussionmentioning
confidence: 99%